Unraveling the Complexity of Childhood Polycystic Kidney Disease: A Case Study of Three Sisters - Ivana Trutin; Lea Oletić; Tamara Nikuševa-Martić (Children, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disorder, estimated to affect 1 in 1000 people. It displays a high level of variability in terms of onset and severity among affected individuals within the same family. In this case study, three sisters (4, 8, and 10 years of age) were suspected of having ADPKD due to their positive family history. While the two younger sisters aged 8 and 4 showed no disease complications and had normal kidney function, the oldest sister was found to have no dipping status on ambulatory blood pressure measurement (ABPM). Two of the sisters were discovered to have a PKD1 mutation, while the third sister aged 8 was heterozygous for TTC21B c.1593_1595del, p. (Leu532del), which is a variant of uncertain significance (VUS). Environmental factors and genetic modifying factors are believed to contribute to the phenotypic variability observed in ADPKD. Identifying and understanding potential genetic and environmental modifiers of ADPKD could pave the way to targeted treatments for childhood ADPKD.